Design, synthesis and antitumor properties of glycosylated antitumor ether lipid (GAEL)- chlorambucil-hybrids. (January 2016) - Idowu, Temilolu; Samadder, Pranati; Arthur, Gilbert; Schweizer, Frank
Highlights: Cytotoxic properties of chlorambucil-glycolipid hybrids was examined. Hybrids exhibit higher activity when compared to individual components. Fusion of pro-apoptotic and apoptosis-independent agents enhances cytotoxicity. Abstract: Glycosylated antitumor ether lipids (GAELs) kill cancer cells and cancer stem cells via a novel, apoptosis-independent mechanism. In contrast, chlorambucil, a drug in clinical use for the treatment of chronic lymphocytic leukemia reacts with nucleophiles within the major groove of DNA, leading to apoptosis. We hypothesized that hybrid molecules that combine apoptosis-dependent and apoptosis-independent mode of actions in a single molecule may lead to enhanced antitumor activity. Here, we describe the antitumor activities of chlorambucil-linked glucosamine-derived glycerolipid hybrids and investigate the role of the chlorambucil moiety and the effect of cationic charge on the hybrid molecule. Three hybrids and two control GAELs were synthesized and their activities against breast (JIMT1, MDA-MB-231, BT474), pancreas (MiaPaCa2) and prostate (DU145, PC3) cancer cell lines were determined using MTS assay. Hybrid3 displayed the most potent activity on DU145 at CC50 of 6.0 μM while hybrid4 displayed the best activity on JIMT1 at 7.5 μM. Hybrid5 exhibited no activity at the highest concentration tested (CC50 >20 μM), underscoring the significance of the cationic charge at C -2 position as previously reported. Although chlorambucil(2) itself showed very little activity against all the six cell lines (CC50 >150 μM), GAELs6 and7 which lack the chlorambucil moiety were consistently less active than3 and4, suggesting that the chlorambucil moiety contributes to the overall activity. The hybrids were however not as active as the parent GAEL1 against MiaPaCa2 whereas6 restored activity comparable to1 .